9+5w-1w=12-6w

Simple and best practice solution for 9+5w-1w=12-6w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+5w-1w=12-6w equation:


Simplifying
9 + 5w + -1w = 12 + -6w

Combine like terms: 5w + -1w = 4w
9 + 4w = 12 + -6w

Solving
9 + 4w = 12 + -6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '6w' to each side of the equation.
9 + 4w + 6w = 12 + -6w + 6w

Combine like terms: 4w + 6w = 10w
9 + 10w = 12 + -6w + 6w

Combine like terms: -6w + 6w = 0
9 + 10w = 12 + 0
9 + 10w = 12

Add '-9' to each side of the equation.
9 + -9 + 10w = 12 + -9

Combine like terms: 9 + -9 = 0
0 + 10w = 12 + -9
10w = 12 + -9

Combine like terms: 12 + -9 = 3
10w = 3

Divide each side by '10'.
w = 0.3

Simplifying
w = 0.3

See similar equations:

| 10m^2-53m+36=0 | | 7x+2x-3x=3(x-8) | | y=2(3)-25 | | .01(900-30x)=9.8x+400 | | 3x^2=288x^2 | | 9+5w-14x=12-6w | | y=3(3)-22 | | 5(2x+6)=4(-5-2x)3x | | x-4=-4x-2 | | 4m-19-11=70 | | 6r-18=30 | | 18=-3y-12 | | 87-x=136 | | 3/8=r2/3 | | (3w+5x-7)(w+7x)= | | X+5=x+11 | | 5x+4x+8-2x-8= | | 4/17 | | y=-5(3)+17 | | 2=(4/p) | | 4(6-4+6)= | | 5x-4=4-4x | | 8+8x=4x+24 | | 3(2z+2.5)-2(2-1)=78 | | (2/3)(-11/8) | | -48+3m=-6(1-4m) | | ln(4x^2-100)-ln(x-2)=0 | | -2p+3=8p-7 | | 9c-3=15c+15 | | 12h+2h-3=5h+1+h | | 2x+5x+20=3x | | (2/3)(-11/8), |

Equations solver categories